What Makes Your Dog Itch? Maybe It Is the Kennel Tick! - Ferrolho, J (2017)
Once upon a time, in a backyard not very far from you, lived a dog named Rex with long fluffy and shiny hair. Rex really loved to play outside, especially with his best friend and owner Jack, a nine-year-old boy. On a perfect spring day, when it was not too cold or too hot, Jack and Rex went for a walk in a green park close by, and when they returned home Jack noticed that his loyal friend was very itchy and was scratching his ear a lot. His first thought was as follows: “Well, there must be some dirt in his ear! After so much rolling on the grass it is normal.” A few days later Jack saw that Rex was very unhappy and started wondering what was happening. He called his mother quickly and they both rushed to see Rex. “Mommy what’s that on Rex’s ear? It seems like a wart! Is Rex sick?” Then his mother said “Hopefully not! You know Jack, these little things are parasites called ticks and they can make Rex itch and feel uncomfortable. I am sure that if you learn more about such small and incredible creatures, you will be amazed because there is more to them than meets the eye…”